2020
DOI: 10.1111/jcmm.15927
|View full text |Cite
|
Sign up to set email alerts
|

Multiple potential targets of opioids in the treatment of acute respiratory distress syndrome from COVID‐19

Abstract: COVID-19 currently represents an ongoing global threat as the development of ARDS during the course of disease may be observed in more than 40% of patients with pneumonia from SARS-CoV-2 infection. 1 ARDS from COVID-19 requires early recognition and a comprehensive management as it can have worse outcomes than ARDS from other causes. Pulmonary fibrosis, thrombotic microangiopathy, pleuritic pain and worsening of respiratory symptoms appear to be factors of a more severe course of disease from the increased inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…12 According to the World Blood Transfusion Association, about 341 antigens have been identified and categorized into 41 blood group systems. 13 ABO blood group system, as discovered by Landsteiner, is the most important blood group system. 14 The sequential additions of carbohydrates to an oligosaccharide backbone resulted in formation of three antigens, including A, B, and H. 15 Adding a terminal residue to the oligosaccharide backbone, creates the H antigen which then acts as a precursor for formation of A and B antigens.…”
Section: Blood Group Antigens and Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…12 According to the World Blood Transfusion Association, about 341 antigens have been identified and categorized into 41 blood group systems. 13 ABO blood group system, as discovered by Landsteiner, is the most important blood group system. 14 The sequential additions of carbohydrates to an oligosaccharide backbone resulted in formation of three antigens, including A, B, and H. 15 Adding a terminal residue to the oligosaccharide backbone, creates the H antigen which then acts as a precursor for formation of A and B antigens.…”
Section: Blood Group Antigens and Diseasesmentioning
confidence: 99%
“…There are a number of carbohydrates and proteins on human red blood cell (RBC) membranes that are known as blood group antigens 12 . According to the World Blood Transfusion Association, about 341 antigens have been identified and categorized into 41 blood group systems 13 . ABO blood group system, as discovered by Landsteiner, is the most important blood group system 14 .…”
Section: Blood Group Antigens and Diseasesmentioning
confidence: 99%
“…However, opioids also present side effects such as diarrhea, hyperalgesia, dysphoria, tolerance and dependence processes, their prolonged use might be associated to immunological system suppression, and high doses of opioids might lead to respiratory depression, exacerbating the poor respiratory condition of those patients ( Boom et al, 2012 ; Franchi et al, 2019 ; Cismaru et al, 2021 ). Patients with high doses of opioids might experience hypercapnia and hypoxia, due to the previously mentioned mechanisms, thus contributing to more severe respiratory symptoms ( LeGrand et al, 2003 ; Ataei et al, 2020 ; Velavan and Meyer, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…In influenza and respiratory syncytial viruses (RSVs), opioids reduce the rate and severity of infection through anti-inflammatory and immunomodulatory functions (Salimi et al, 2013). Cismaru et al (2021) previously reported that none of the opioid medications are superior to others in treating dyspnea. So, oxycodone, hydromorphone fentanyl dihydrocodeine, diamorphine, and oral or parenteral morphine can be used for this purpose.…”
Section: Discussionmentioning
confidence: 99%